Implementasi Kewenangan Badan Narkotika Nasional (BNN) Aceh dalam Memberikan Rehabilitasi Terhadap Pelaku Penyalahgunaan Narkotika - Muhammad Willy; Melwani (Jurisprudensi: Jurnal Ilmu Hukum, 2025)
This study aims to analyze the implementation of the authority of the National Narcotics Agency of Aceh Province in providing rehabilitation for narcotics abusers, to identify the obstacles encountered, and to explain the efforts undertaken to optimize the implementation of rehabilitation. This research employs a qualitative method with a socio-juridical approach. Data were obtained through library research and field research in the form of interviews with relevant parties, and were then analyzed descriptively and analytically. The findings show that BNN Aceh has a strategic authority in the implementation of rehabilitation, which is carried out through the stages of assessment, medical rehabilitation, social rehabilitation, and follow-up guidance. However, the implementation of this authority has not yet been optimal due to several obstacles, including low public participation and understanding, stigma toward narcotics abusers, limited facilities and infrastructure, a shortage of human resources, insufficient budget allocation, and suboptimal inter-agency coordination. To address these obstacles, BNN Aceh has undertaken various efforts through strengthening public outreach, cross-sectoral coordination, community empowerment, as well as the application of social, situational, and community-based crime prevention approaches. This study confirms that the effectiveness of rehabilitation is determined not only by the normative legal authority, but also by institutional capacity and social support in its implementation.